Aggregated GPS tracking of vehicles and its use as a proxy of traffic-related air pollution emissions. (October 2016) - Chen, Shimon; Bekhor, Shlomo; Yuval,; Broday, David M.
Abstract: Most air quality models use traffic-related variables as an input. Previous studies estimated nearby vehicular activity through sporadic traffic counts or via traffic assignment models. Both methods have previously produced poor or no data for nights, weekends and holidays. Emerging technologies allow the estimation of traffic through passive monitoring of location-aware devices. Examples of such devices are GPS transceivers installed in vehicles. In this work, we studied traffic volumes that were derived from such data. Additionally, we used these data for estimating ambient nitrogen dioxide concentrations, using a non-linear optimisation model that includes basic dispersion properties. The GPS-derived data show great potential for use as a proxy for pollutant emissions from motor-vehicles. Highlights: A methodology for examining ICT-derived traffic volumes is presented. Whereas some problems were found, in general ICT data were reliable. Traffic was reported in cells devoid of roads, due to scattering from adjacent cells. ICT data have better spatiotemporal availability than more traditional data sources. The ICT-based traffic volumes were successfully used as a proxy for NO2 emissions.